Efektifitas Pembelajaran Dengan Pendekatan Contextual Teaching And Learning (CTL) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis - Murnaka, Nerru Pranuta; Anggraini, Betta; Surgandini, Arumella (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
This research is motivated by students' mathematical problem-solving abilities. One way to improve students' mathematical problem-solving abilities is with the CTL learning approach. The purpose of this research is: 1) to know whether the average ability of mathematical problem solving of students who get learning with CTL approach is higher than the average problem-solving abilities of mathematical students who obtain conventional learning; 2) to find out whether the average mathematical problem-solving ability of the students who acquired the learning with Contextual Teaching and Learning (CTL) approach is higher than the minimum criterion value (KKM). This research type is quasi-experiment. The research design used is Nonequivalent Control Group Design. This research was conducted at SMP Negeri 1 Simpang Renggiang, East Belitung Regency in the academic year 2015/2016. Sampling was done by cluster random sampling. The sample in this research is class VII. 2 as the experimental class and class VII.3 as the control class. The research instrument used is a valid test instrument in the form of a matter of pretest and posttest in the form of a description. Data were analyzed using a non-parametric statistic test. The results of the research have shown that the average problem-solving ability of students who acquire mathematics learning with CTL approach is better than students who follow the conventional mathematics learning, the average problem-solving ability of mathematical students who gain learning with CTL approach less than or equal with KKM.Â Keywords: Mathematical problem solving, CTL approach, quasi-experiment, cluster random sampling